Elevated Expression of the Cerebrospinal Fluid Disease Markers Chromogranin A and Clusterin in Astrocytes of Multiple Sclerosis White Matter Lesions. Issue 1 (January 2016) - van Luijn, Marvin M.; van Meurs, Marjan; Stoop, Marcel P.; Verbraak, Evert; Wierenga-Wolf, Annet F.; Melief, Marie-José; Kreft, Karim L.; Verdijk, Robert M.; 't Hart, Bert A.; Luider, Theo M.; Laman, Jon D.; Hintzen, Rogier Q.
Abstract : Using proteomics, we previously identified chromogranin A (CgA) and clusterin (CLU) as disease-related proteins in the cerebrospinal fluid (CSF) of patients with multiple sclerosis (MS). CgA and CLU are involved in cell survival and are implicated in neurodegenerative disorders and may also have roles in MS pathophysiology. We investigated CgA and CLU expression in lesions and nonlesional regions in postmortem brains of MS patients and controls and in the brains of marmosets with experimental autoimmune encephalomyelitis. By quantitative PCR, mRNA levels of CgA and CLU were elevated in white matter but not in grey matter of MS patients. In situ analyses showed greater expression of CgA and CLU in white matter lesions than in normal-appearing regions in MS patients and in the marmosets, primarily in or adjacent to perivascular spaces and inflammatory infiltrates. Both proteins were expressed by glial fibrillary acidic protein-positive astrocytes. CgA was more localized in astrocytic processes and endfeet surrounding blood vessels and was abundant in the superficial glia limitans and ependyma, 2 CSF-brain borders. Increased expression of CgA and CLU in reactive astrocytes in MS white matter lesions supports a role for these molecules as neuro-inflammatory mediators and their potential as CSF markers of active pathological processes in MS patients.